Elucidating conserved sub-units from beta-coronavirus species for the creation of novel, cross-clade, and stable chimera sars-cov-2 spike proteins as future proof vaccine candidates - Susu, Wang (2023)
The COVID-19 pandemic caused by the SARS-CoV-2 outbreak triggered extensive scientific research. In this thesis, the spike (S) protein of the SARS-CoV-2 was studied in depth to gain useful insights to create a future proof vaccine. The structural information and structural stability of chimeric beta-coronavirus S proteins were investigated using bioinformatics techniques, structural predictions and molecular dynamics simulations. The study initially targeted the entire S protein of chimeric betacoronaviruses, but due to certain constraints, the study shifted the direction onto conserved regions of the S2 subunit only to generate chimeric sequences from different beta coronaviruses, in order to obtain vaccine candidates with broad immune coverage. For practicality, ten chimeric S2 sequences were carefully selected to study chimeric viral protein structures. This study used AlphaFold2 to predict 3D structures of the chimeric S2 protein sequences. Molecular dynamics simulations further elucidated their structural stabilities. The results lay the foundation for novel future proof vaccine design.